Drivers of the variability of dimethylsulfonioproprionate (DMSP) and dimethylsulfoxide (DMSO) in the Southern North Sea. (1st March 2021) - Royer, C.; Borges, A.V.; Lapeyra Martin, J.; Gypens, N.
Abstract: The influence of abiotic and biotic factors on the concentration of dimethylsulfoniopropionate (DMSP) and dimethylsulfoxide (DMSO) was investigated and compared during two annual cycles in 2016 and 2018 in the Belgian coastal zone (BCZ) in the southern North Sea at five fixed stations. These stations covered a near-offshore gradient from stations close to the mouth of the Scheldt estuary to most offshore stations. Significant differences of Chlorophyll- a (Chl- a ) concentrations were observed between the two years with higher values in early spring 2018 (due to better light and nutrient conditions coupled to colder temperatures) and in summer 2018 (due to warmer conditions) compared to 2016. Nevertheless, the seasonal and spatial DMSP and DMSO (DMS(P, O)) patterns, as well as the yearly average were nearly identical in 2016 and 2018. This can be explained by the fact that the phytoplankton groups responsible for the large differences in Chl- a in 2018 and 2016 were low DMSP-producers characterized by several diatom and dinoflagellate species, occurring in early spring and summer. Further, the Prymnesiophyceae Phaeocystis globosa, occurring in late spring and responsible of most of DMS(P, O) measured in the area, reached similar biomass both years. The DMSP:Chl- a ratio obtained from the field measurements were similar to those previously published for the main observed phytoplankton groups, but more differences were observed for the DMSO:Chl- a ratio. DMS(P, O) estimations based on Chl- a linear regressions for the whole dataset need to account on two relationships discriminating the low and high-DMSP producing species. Highlights: Chl- a are significatively different between the years 2016 and 2018 during the early spring and summer diatom blooms. The higher incident light coupled to colder winter and higher nutrients inputs explained these variations. The seasonal DMS(P, O) concentrations are nearly identical due to the dominance of low-DMSP producing species of diatoms. DMS(P, O) estimations need to account on two relationships discriminating the low and high-DMSP producing species.